Knowledge ecoliteracy of junior high school students towards Toba Caldera UNESCO Global Geopark - Rosdiana, Erika; Suyanti, Retno Dwi; Manurung, Binari (Universitas Islam Negeri Sumatera Utara, 2025)
This study aimed to determine the level of knowledge ecoliteracy of junior high school students towards Toba Caldera UNESCO Global Geopark (TCUGGp) was conducted. The research respondent was 78 people, including 28 students from Toba regency and 25 students each from North Tapanuli and Samosir regencies. The research instrument comprised 30 questions and was developed from five indicators, namely factual issues of environmental problems, the impacts, the factors causing environmental problems, efforts that can be made to minimize the impact of environmental degradation, flora-fauna biodiversity and the name of geosites. Data analysis used descriptive and inferential methods. The research results indicated that the knowledge ecoliteracy of junior high school students remains relatively low (X̅ = 58.28). ANOVA test results showed a significant difference in students'knowledge ecoliteracy among the three regencies (F = 3.24; P = 0.04). Further findings revealed that junior high school students have limited understanding in the factors causing environmental problems, efforts to minimize the impacts of environmental degradation, and more specifically in the diversity of rare and endemic of flora and fauna, as well as in geosite names. This research finding recommends that IPA-biology learning in junior high schools especially at the topic biodiversity, interactions between living organisms and the environment, and environmental changes should be conducted by using more innovative learning models, as well as its media, learning resources, and assessments that refers to local social scientific issues so that ensuring the creation of meaningful learning.